Inflação para as famílias de renda muito baixa, renda média e renda alta: uma análise entre 2017 e 2024 - Mazine, Matheus Henrique (Universidade Federal de São Carlos, 2025)
Inflation is a phenomenon of great economic relevance, as it directly affects the population's purchasing power and macroeconomic stability. However, its impact is not homogeneous across different income brackets. Based on this premise, this study aims to analyze, in a descriptive and exploratory manner, the behavior of consumer inflation for very low-income, middle-income, and high-income families in Brazil, according to the segmentation proposed by the Institute of Applied Economic Research (IPEA). To achieve this objective, descriptive and exploratory statistics techniques were used, allowing the identification of patterns and trends in inflation behavior over the period from 2017 to 2024. The study considered the main components of the consumer basket of the different social classes, seeking to understand which groups of goods and services exert the greatest influence on the inflation perceived by each segment of the population. The results indicate that very low-income families face more volatile inflation when compared to middle- and high-income families. This greater variability is largely associated with the significant burden that items such as food and housing have on the budgets of poorer families. The increase in the prices of these essential goods has a more severe impact on this segment of the population, which allocates a greater proportion of its income to such expenses. In contrast, higher-income families tend to be less affected by variations in these segments and are more impacted by fluctuations in the prices of non-essential consumer goods and services. Thus, the study reinforces the importance of targeted public policies that take into account the heterogeneity of the inflationary impact among different social groups. Understanding the particularities of inflation for each income bracket is essential for improving inflation control strategies and for formulating measures that minimize the adverse effects on the most vulnerable segments of the population.
Inflation for very low-income, middle-income and high-income households: an analysis between 2017 and 2024
Keywords: Preços; Renda; Consumo; Prices; Income; Consumption; CIENCIAS SOCIAIS APLICADAS::ECONOMIA